2007
DOI: 10.1007/s00441-007-0544-x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular localization of a putative Na+/H+ exchanger 3 during ontogeny in the pronephros and mesonephros of the Japanese black salamander (Hynobius nigrescens Stejneger)

Abstract: The cloning of cDNA and an examination of the tissue distribution of Na(+)/H(+) exchanger 3 (NHE3) were carried out in the Japanese black salamander, Hynobius nigrescens. The cellular localization of Hynobius NHE3 was examined by in situ hybridization and immunohistochemistry during ontogeny in the nephron of the pronephros and mesonephros of the salamander. The partial amino acid sequence of Hynobius NHE3 was 81% and 72% identical to rat NHE3 and stingray NHE3, respectively. Hynobius NHE3 mRNA and protein wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Anti-vacuolar type H + -ATPase α-subunit antiserum was raised by immunizing Japanese white rabbits with a synthetic peptide, NH 2 -AEMPADSGYPAYLGAR-COOH, as described previously (Hayashi et al, 2000). This antiserum specifically recognizes intercalated cells of the late distal tubule and the collecting duct of the amphibian kidney (Uchiyama and Yoshizawa, 2002;Konno et al, 2006;Konno et al, 2007;Kumano et al, 2008).…”
Section: Antibodiesmentioning
confidence: 99%
“…Anti-vacuolar type H + -ATPase α-subunit antiserum was raised by immunizing Japanese white rabbits with a synthetic peptide, NH 2 -AEMPADSGYPAYLGAR-COOH, as described previously (Hayashi et al, 2000). This antiserum specifically recognizes intercalated cells of the late distal tubule and the collecting duct of the amphibian kidney (Uchiyama and Yoshizawa, 2002;Konno et al, 2006;Konno et al, 2007;Kumano et al, 2008).…”
Section: Antibodiesmentioning
confidence: 99%
“…The mesonephric nephron of the Japanese black salamander was previously investigated in detail (Kumano et al, 2008). ENaCα immunoreactivity was observed in the apical cell membrane of the late distal tubule (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Using double immunostaining of ENaCα and the vacuolar‐type H + ‐ATPase, this study showed immunohistochemically that Hynobius ENaC α‐subunit protein and vacuolar‐type H + ‐ATPase are localized in the apical membrane of principal cells and intercalated cells, respectively, along the late segment of the distal tubule to collecting duct in the kidney of H. nigrescens as well as in the toad kidney (Konno et al, 2007). Our previous study showed that NHE3 mRNA and protein were only present in early segment of the distal nephron in H. nigrescens (Kumano et al, 2008). Taken together, this study demonstrates that transepithelial sodium transport in the late distal nephron occurs principally via NHE3 and ENaC in early and late segments of the distal tubule of H. nigrescens , respectively.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations